Analisis Biaya Manfaat Taman Kuliner Condongcatur, Depok Sleman Yogyakarta - , Nur Fitri Mutmainah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main agenda of current development is emphasized to the local economic development. Sleman regency chose Taman Kuliner as one of potential local economic activities aiming at relocating the sidewalk sellers. The previous goal is not easily achieved as what expected. Based on previous studies and direct observation by the writer, the Taman Kuliner decreases year by year. Therefore, the writer thinks that a research on Benefit Cost Analysis of Condongcatur Taman Kuliner is important to conduct. Qualitative descriptive methodology was employed in this research. In benefit cost analysis, a policy is said to be good whenever it gives greater benefit than the spent cost. The analysis of this research found that there are three actors performing important roles in the development of Taman Kuliner Condongcatur: Sleman regency government, stall tenants, and people surround the court. Of the actors, there was benefit cost which was spent and received as the consequence of Taman Kuliner existence. To Sleman regency government, the cost was spent for development investment was as much as Rp. 3.5 billion and operational realization in 2012 was as much as Rp. 207.590.00,-, while the received benefit in 2012 was as much as Rp. 110.920.000,- . The net benefit cost received by Sleman regency government was negative Rp. 271.670.000,-. To the stall tenants, consisting of eighteen people, the spent cost as the capital was as much as Rp. 289.716.000,- , while the received benefit was Rp. 347.400.000. The net benefit cost received by stall tenants was positive Rp. 57.684.000,-. The indirect cost which cannot be measured with money was the peopleâs losing job. The indirect benefits were labor force absorption and the availability of means and infrastructures of art and socio-cultural performance to the society. Based on the benefit cost calculation assumption, it was found that benefit will be received more than the spent cost if the stall tenants perform the economy activities actively and regularly in the Taman Kuliner. To be able to achieve the expected goal, a forum is needed: stakeholders (government, private entrepreneur, and society) are expected to have a dialog to plan the activity programs for local economy increase.